Analysis of the Application of Financial Accounting Standards for Entities without Public Accountability in the Presentation of Financial Reports - Venna Maulida Mustika; Rahmiatul Aula (Universitas Serambi Mekkah, 2024)
Small and Medium Enterprises (SMEs) have a very important role for the economy of Indonesia, because the development of SMEs increases the absorption of the highest labor force compared with other business units. This study aims to analyze the application of accounting at SMEs and to determine whether SMEs have prepared financial statements in accordance with Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). Methods of data collection in this study used the method of documentation, observation and direct interviews with respondents. This study uses descriptive - comparative analysis techniques to compare the application of accounting in the preparation of financial statements of SMEs and SAK ETAP. The results showed that the implementation of accounting conducted by the perpetrators of SMEs at shrimp earthen dam is still very simple and the perpetrators have not prepared financial statements in accordance with SAK ETAP due to lack of knowledge of SMEs regarding SAK ETAP.